Performance of the Cas9 Nickase System in Drosophila melanogaster - Ren, Xingjie (Genetics Society of America, 2014)
Recent studies of the Cas9/sgRNA system in Drosophila melanogaster genome editing have opened new opportunities to generate site-specific mutant collections in a high-throughput manner. However, off-target effects of the system are still a major concern when analyzing mutant phenotypes. Mutations converting Cas9 to a DNA nickase have great potential for reducing off-target effects in vitro. Here, we demonstrated that injection of two plasmids encoding neighboring offset sgRNAs into transgenic Cas9(D10A) nickase flies efficiently produces heritable indel mutants. We then determined the effective distance between the two sgRNA targets and their orientations that affected the ability of the sgRNA pairs to generate mutations when expressed in the transgenic nickase flies. Interestingly, Cas9 nickase greatly reduces the ability to generate mutants with one sgRNA, suggesting that the application of Cas9 nickase and sgRNA pairs can almost avoid off-target effects when generating indel mutants. Finally, a defined piwi mutant allele is generated with this system through homology-directed repair. However, Cas9(D10A) is not as effective as Cas9 in replacing the entire coding sequence of piwi with two sgRNAs.